Understanding the World of Industry and Business from the Perspective of Career Guidance and Counseling - Korompot, Salim; Wantu, Tuti; Alwi, Nurul Maulida (Bisma The Journal of Counseling, 2022)
The purpose of this research is to understand the world of industry and business (IDUKA) which is indispensable as a basis for increasing individual competence when entering the career world. Career guidance and counseling in this context aims to provide an understanding of several theories and competencies that must be improved, so that each individual can develop optimally in today's changing times to be more advanced. The current research method is a literature review study, which is a written summary of several studies and articles from journals, books and several career theories and information that have been reviewed. Although career guidance and counseling is not the only solution to provide an understanding of preparation to enter the world of industry and business, career guidance and counseling services can open up horizons of thinking as basic knowledge for the world of industry and business that can be understood.